The Influence of Green Marketing, Brand Image, and Price Perception on Consumers’ Purchasing Decisions of Le Minerale Products - Sekundus Klemens Kerans; Mariana Puspa Dewi Dewi (Journal of Educational Management Research, 2026)
This study aims to examine the effects of green marketing, brand image, and price perception on consumers’ purchasing decisions of bottled drinking water products. A quantitative research approach was employed using purposive sampling, resulting in 103 respondents. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics 27. The results show that, partially, green marketing and brand image have a positive but insignificant effect on purchasing decisions, while price perception has a positive and significant effect and emerges as the most dominant variable. Simultaneously, green marketing, brand image, and price perception significantly influence purchasing decisions. These findings imply that consumers tend to prioritize price considerations over environmental attributes and brand image when making purchasing decisions. Therefore, companies should maintain competitive pricing strategies while integrating green marketing initiatives and strengthening brand image to enhance overall purchasing appeal and market competitiveness.